Comparison of built environment adaptations to heat exposure and mortality during hot weather, West Midlands region, UK. (February 2018) - Taylor, Jonathon; Wilkinson, Paul; Picetti, Roberto; Symonds, Phil; Heaviside, Clare; Macintyre, Helen L.; Davies, Michael; Mavrogianni, Anna; Hutchinson, Emma
Abstract: There is growing recognition of the need to improve protection against the adverse health effects of hot weather in the context of climate change. We quantify the impact of the Urban Heat Island (UHI) and selected adaptation measures made to dwellings on temperature exposure and mortality in the West Midlands region of the UK. We used 1) building physics models to assess indoor temperatures, initially in the existing housing stock and then following adaptation measures (energy efficiency building fabric upgrades and/or window shutters), of representative dwelling archetypes using data from the English Housing Survey (EHS), and 2) modelled UHI effect on outdoor temperatures. The ages of residents were combined with evidence on the heat-mortality relationship to estimate mortality risk and to quantify population-level changes in risk following adaptations to reduce summertime heat exposure. Results indicate that the UHI effect accounts for an estimated 21% of mortality. External shutters may reduce heat-related mortality by 30–60% depending on weather conditions, while shutters in conjunction with energy-efficient retrofitting may reduce risk by up to 52%. The use of shutters appears to be one of the most effective measures providing protection against heat-related mortality during periods of high summer temperatures, although their effectiveness may be limited under extreme temperatures. Energy efficiency adaptations to the dwellings and measures to increase green space in the urban environment to combat the UHI effect appear to be less beneficial for reducing heat-related mortality. Highlights: Built environment characteristics may affect population exposure to excess heat. Housing and land surface changes may alter heat exposure and heat-related mortality. Installing external shutters may reduce heat-attributable deaths by 30–60%. Shutter installation and energy efficiency retrofit may reduce mortality by 52%. The Urban Heat Island may contribute to 21% of heat mortality.